IMMU-03. DEVELOPMENT OF CYTOMEGALOVIRUS (CMV) BASED DNA VACCINES FOR GBM USING THE UNITE PLATFORM. (5th November 2018) - Adhikari, Amit; Weiss, Ido; Marketon, Anthony; Toll, Barbara; Heiland, Teri
Abstract: Glioblastoma (GBM) remains an aggressive, deadly disease in brain cancer, with the median survival of 15 months remaining unchanged for decades. Using our investigational UNITE platform, we are developing a DNA vaccine using CMV antigens. The UNITE platform is based, in part, on a lysosomal targeting technology which can result in increased antigen presentation, a balanced T cell response, and subsequent immunologic benefit. The presence of CMV proteins in GBM offers a unique opportunity to specifically target tumor cells, unlike other cancers. This targeting approach, in the vaccination of mRNA transfected autologous dendritic cells, was employed by Drs. John Sampson and Duane Mitchell, at Duke University in a Phase I trial. Additionally, an ongoing phase II trial, run by Dr. Mitchell at University of Florida, is leveraging the same targeting approach. Promising results were observed using pp65 (a CMV structural protein) loaded dendritic cells in the phase I clinical trial (Clinical Cancer Research, 2014, Pg-2684). Our objective to develop the DNA vaccine is to achieve both a lower cost and quick turnaround time by eliminating need to isolate and culture autologous dendritic cells and to explore other ways of vaccine improvement. We have tested CMV antigens with UNITE platform in mice using intradermal injection followed by electroporation and found robust T cell response. We are also developing orthotopic GBM model in syngeneic mice and to closely mimic human GBM where tumor cells express CMV proteins, we have made stable murine glioma cell lines expressing pp65 or pp65 and gB fused with luciferase as reporter. Therapeutic studies are ongoing in the intracranial GBM mouse models. We believe that if successful, DNA vaccines using CMV proteins as targets, either alone or in combination with other therapies, will be a powerful and cost effective treatment to fight this dreadful cancer.